Qualitative Analysis of Antibiotic Use in Community Acquired Pneumonia Cases in Inpatients at a Government Hospital Batam City - Oktaviani, Fifin; Hamid, Hazrina Binti (Indonesian Journal of Advanced Research, 2024)
Community Acquired Pneumonia (CAP) is caused by pathogenic infections such as bacteria and fungi acquired outside the hospital, the main therapy given to pneumonia patients is antibiotics. The irrationality of antibiotics will lead to antibiotic resistance. This study aims to determine the description and evaluation of the appropriateness of antibiotic use in CAP patients in inpatient a government hospital Batam  period January 2023 to December 2023 using the PPAB 2021, IDSA 2019 and PDPI 2021 therapy guidelines. This research method is cross-sectional with a retrospective data collection technique using medical records, descriptive data analysis. The results of the study of 34 samples of the description of the use of antibiotics that were most often prescribed were Ceftriaxone at 35.28%. The results of the evaluation of accuracy based on the PPAB 2021, IDSA 2019 and PDPI 2021 guidelines obtained the correct type of antibiotic of 85.3%, the correct dose of 91.2%, the correct route and time of administration of 100% and the correct interval of administration of 82.4%.